2018
DOI: 10.1108/jgr-05-2018-0014
|View full text |Cite
|
Sign up to set email alerts
|

Organizational cynicism and employee performance

Abstract: Purpose Organizational cynicism is a growing trend in contemporary organizations. However, its impact on employee performance remains understudied. The purpose of this study is to address this gap by investigating the effect of three dimensions of organizational cynicism (cognitive, affective and behavioral cynicisms) on employee performance. The study also investigates the moderating effect of employee engagement on the relationship between three types of organizational cynicism and employee performance. De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 52 publications
2
8
0
Order By: Relevance
“…The modern business environment nowadays is seeing an increase in demand for ethical CSRs (37,38). Ethical CSR is related to those activities which are not specified by the law but are expected to be done by corporations for the respect toward individuals, prevent the loss, and minimizing societal damage (39,40).…”
Section: Ethical Csrmentioning
confidence: 99%
“…The modern business environment nowadays is seeing an increase in demand for ethical CSRs (37,38). Ethical CSR is related to those activities which are not specified by the law but are expected to be done by corporations for the respect toward individuals, prevent the loss, and minimizing societal damage (39,40).…”
Section: Ethical Csrmentioning
confidence: 99%
“…The research findings of Luong (2012) that The results of this study indicate that employee engagement moderates the relationship between organizational cynicism and employee performance positively. The differences between the research of Chen & Kao (2012) and Arslan (2018) indicate that employee engagement deserves to be tested further as a moderating variable in the relationship between perceived organizational support and employee performance. Besides that, there are other findings that can be a research gap that can be considered by the authors using employee engagement as a moderating variable.…”
Section: General Managementmentioning
confidence: 86%
“…exhaustion, is the most significant predictor of task performance, while cynicism is the most powerful predictor of contextual performance. Arslan (2018) indicated that when employees express negative attitudes at work, their performance, engagement and creativity are more likely to reduce. Abraham (2000) argued that cynical attitudes stem from employees' perception of a lack of trust, confidence and support in organization and influence employees' satisfaction, commitment and performance.…”
Section: Cynicism and Task Performancementioning
confidence: 99%